Evaluation of Awareness levels about foot care and its impact on foot care practices among Diabetic Individuals in Pakistan - HAMZA AZIZ,; FATIMA HAYAT,; MUHAMMAD IBRAHIM,; MASHAL AZIZ,; MAHNOOR KHURRAM,; RIMSHA RANA,; ROHMA SHAHBAZ, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: This research covers a very important topic in today’s time, diabetic foot care. To prevent its complications, an in depth understanding of awareness levels and practices about foot care among diabetic individuals is very important. Aim: To assess awareness levels about foot care and its impact on foot care practices among diabetic individuals. Methods: The population of the study was composed of the diabetic patients coming to outpatient departments in a tertiary care hospital in Rawalpindi. The study was carried out over a period of 6 months from January 2024 to June 2024. The participants were enrolled through non-probability convenience sampling. 266 diabetic patients participated in the research who met the inclusion criteria. Data was collected by using a structured questionnaire. Results: A total of 266 valid responses were received that were analyzed using SPSS v25, out of which 124 (46.6%) are males and 142 (53.4%) are females. The analysis showed that there is a weak positive correlation between the total knowledge and total practice scores of 0.174 (p value 0.004). Conclusion: Older patients, male population, patients with other chronic diseases, patients who received a formal education about diabetes foot complications, and patients having diabetes for more than 20 years show greater knowledge and better practice to protect from diabetic foot complications. It is imperative to inform people with diabetes that proper foot care is crucial in preventing the formation of wounds. Keywords: Diabetes Mellitus, Diabetic Foot, Chronic diseases, foot care practices